Labor and Product Market Deregulation : Partial, Sequential, or Simultaneous Reform? - Berger, Helge (IMF Working Papers; Working Paper ;, 2005)
This study explores the effects of labor and product market deregulation on employment growth. Our empirical results, based on an OECD country panel from 1990-2004, suggest that lower levels of product and labor market regulation foster employment growth, including through sizable interaction effects. Based on these findings, the paper develops a theoretical framework for evaluating deregulation strategies in the presence of reform costs. Optimal deregulation takes various forms depending on the deregulation costs, the strength of reform interactions, and the perspective of the policymaker. Unless deregulation costs are very asymmetric across markets, optimal deregulation requires some form of coordination.